ANALYSIS OF CONTEXTUAL MEANING AND MORAL VALUES ON STILL NOT GETTING ANY ALBUM BY SIMPLE PLAN - Tjitra Ramadhani; Rima Amelia (INTERAKSI : Jurnal Kependidikan, 2013)
Song is a literary works which is more understandable and more familiar in human’s life. Actually, song does not only consist of musics and set of lyrics, but also something that give good impression to the listeners in order that the listeners get moral value on it. Simple Plan are one of pop punk band who comes from Canada, they have released 4 album since 2002 up to 2011. Though they are pop punk band, but their song and even the music are easy to listen. It makes their listeners love their songs. Still not getting any is one of the their album, it was released on october, 2004 . In this study, the researcher discusses and explains about the contextual meaning and moral values on that album. Qualitative research is used as research design in this study because, in this study is related to literature which explain this study descriptively to find out the contextual meaning and the moral value on “Still Not Getting Any” album by Simple Plan. This source of this study is taken from Simple Plan songs on StillNot Getting Any that consists of 11 songs, they are; Shut Up !, Welcome, To My Life, Perfect World, Thank You,Me Against The World,Crazy, Jump, Every time, Promise, One and Untitled.As the result the contextual meaning on Still Not Getting Any album by Simple Plan , almost all of the song lyric in this album tells about the problems in the song writer’s life. It also tells about how to be himself to face every situation and problem in his life. Then, the result of moral value found on Still Not Getting Any album by Simple Plan, there are eight kinds moral value, they are; loyalty, bravery, honesty, confidence, respect, forbearance, love and knowledgeable. From 11 songs above confidence, love and bravery that are the most kind of moral value that appearance in that album. At last, after interpretating and analyzing contextual meaning and moral value on this album, the researcher gives conclussion and suggestion. The conclussion is related to the data that has been analyzed and the suggestion is related to how to comprehend the literary work in order to get knowledge particularly which related to the way in analyzing the contextual meaning and the moral value especially in analyzing song.